Medical and sociological assessment of endodontic treatment on children’s dental admission (Эндодонтия Today, 2020)
In the article the results of medical and sociological research, conducted with a view to assessing the Endodontic treatment of chronic periodontal disease apical permanent teeth with incomplete formation of roots of children's dentists, pediatricians, residing on the territory of Russia and CIS are stated. In this connection, an anonymous questionnaire survey of 255 children's dentists was conducted in omsk, St.-Petersburg and Minsk. These cities were selected as economically stable, which have got their own large medical universities with dental faculties. As a result of questioning revealed significant differences in the provision of dental care for children's population in different cities of Russia and CIS countries on the use of means and methods for the treatment of chronic apical forms of periodontal disease.